Pengembangan Instrumen Penilaian Higher Order Thinking Skills (HOTS) Pada Mata Pelajaran Korespondensi Kelas X OTP Di Smk Negeri 1 Jombang - Siti Aisah; Triesnina Pahlevi (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
The purpose of this study was determine  the process of developing Higher Order Thinking Skills (HOTS) assessment instruments in OTP Class X Correspondence Subjects at SMK Negeri 1 Jombang, the quality of Higher Order Thinking Skills (HOTS) assessment instruments, and high-level thinking skills of students. Using R&D methods. The research model was adapted based on Sugiyono's development model which consisted of 7 steps. The study was conducted on 69 students of class X OTP 1 and 2 of SMK Negeri 1 Jombang. The questions consist of 36 multiple choice questions with 5 alternative answer choices. Based on the results of the validation of three experts validator matei, evaluation, and language declared eligible to be tested. based on data analysis, the validity of the questions compared to r table 0.236 there are 25 valid questions and 11 invalid questions, the reliability value of the difficulty of the questions is 0.667 with the category of "high", the level of difficulty of the questions has an average category of "medium", for distinguishing power questions there are 25 items that can be used, and not all questioners can function well, there needs to be revisions. From the overall values obtained the average value of students is 56.7 which belongs to the category of "sufficient" in the ability to think at a high level. Thus, the final product of the HOTS assessment instrument is 25 items.